PENINGKATAN NILAI KARAKTER GOTONG ROYONG MELALUI PEMANFAATAN MEDIA VIDEO ANIMASI PADA SISWA KELAS 3 SD NEGERI 3 PANDEAN NGEMPLAK BOYOLALI - Sinatrya Tyas Puspita; Suyitno; Kiswoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Puspita, Sinatrya Tyas. 2026. Improving Mutual Cooperation Character Values Through the Use of Animated Video Media in 3rd Grade Students of SD Negeri 3 Pandean Ngemplak Boyolali. Thesis. Elementary School Teacher Education Study Program, Faculty of Education, Universitas PGRI Semarang.This research is motivated by the low mutual cooperation (gotong royong) character values among 3rd-grade students at SD Negeri 3 Pandean, as evidenced by students' egocentric attitudes, lack of cooperation in groups, and the use of conventional and monotonous learning methods. The main objective of this study is to determine the improvement of mutual cooperation character values through the utilization of animated video media in 3rd-grade students of SD Negeri 3 Pandean Ngemplak Boyolali during the odd semester of the 2025/2026 academic year.This research is a Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 29 students from the 3rd grade. Data collection techniques were carried out through behavioral observations, knowledge tests, and skill assessments. The media used in the intervention included the animated video "Adit Sopo Jarwo" and animated fables from the "Riri Cerita Anak Interaktif" channel, which focus on themes of helping others and mutual cooperation.The results showed a significant improvement in each cycle. In the initial condition (Pre-cycle), the average score for students' knowledge was 55.2, attitude was 58.4, and skills were 53.9, with a completion rate of only 13.8%. After the action in Cycle I, the average scores increased to: knowledge 65.5, attitude 67.1, and skills 60.7. In Cycle II, the improvement reached satisfactory results with an average knowledge score of 80.2, attitude of 83.4, and skills of 85.7. The conclusion of this research is that the use of animated video media effectively improves students' mutual cooperation character values in terms of knowledge, attitudes, and skills.